Application of chemometrics in identifying sources of organic contaminants in Langat river basin / Mohamad Rafaie Mohamed Zubir - Mohamed Zubir, Mohamad Rafaie (2015)
With the rapid economic development in Malaysia, environmental pollution has become a major concern, particularly pollution by organic contaminants. Monitoring their temporal and spatial distribution resulted in a large and complicated datasets. It is therefore necessary to apply chemometric techniques to the dataset in order to extract meaningful information and identify the possible sources of these organic contaminants. In this study, the distribution of 13 organic contaminants (polycyclic aromatic hydrocarbons (PAHs), sterols, pesticides (chlorpyrifos), and phenol) in nine monitoring sites along Langat River Basin were monitored from February 2012 to January 2013 on a monthly basis. The analysis of these organic contaminants from surface water was extracted using tandem solid phase extraction (SPE) and analyzed using various chromatographic techniques. The datasets were subjected to chemometric techniques namely hierarchical agglomerative cluster analysis (HACA), discriminant analysis (DA), principal component analysis (PCA) and the factor analysis (FA), to evaluate of possible contamination sources and compared to the inventory of local activities provided by Department of Environmental (DOE), Malaysia. Evaluation on the temporal distribution of these organic contaminants showed that significant variation of PAHs, sterols and phenol during wet weather season (November to April) could be due to dilution factor whereby greater amount of water discharged into the river and intense rainfall could erode the topsoil and carry the accumulated contaminants by surface runoff. By applying HACA, the selected sampling sites were grouped into three clusters which can be correlated to the level of contamination (low, moderate and high contamination sites). Using DA, the contaminants in Langat River could be divided into three sources: domestic sewage/urban discharges, industrial activities and socio-economic activities based on the local activities identified by the Department of Environment (DOE), Malaysia.Forward and backward stepwise DA was able to discriminate two and five organic contaminants variables, respectively, from the original 13 selected variables. The five significant variables identified using backward stepwise DA were fluorene, pyrene, stigmastanol, stigmasterol and phenol. PCA and FA (varimax functionality) were used to identify the possible sources of each organic contaminant based on the inventory of local activities. Five principal components were obtained with 66.5% of the total variation. Result from FA indicated that PAHs (pyrene, fluorene, acenaphthene, benzo[a]anthracene) originated from industrial activity and socio-economic activities; while sterols (coprostanol, stigmastanol and stigmasterol) were asscosiated to domestic sewage and local socio-economic activities. The occurrence of chlorpyrifos was correlated to agricultural activities, urban and domestic discharges. This study showed that the application of chemometrics on the distribution of selected organic contaminants was able to trace the sources of contamination in surface water. In addition, selected pharmaceuticals known as emerging contaminants were determined in samples of surface water of Langat River Basin. Thus, a HPLC separation of six pharmaceuticals (caffeine, acetaminophen, carbamazepine, naproxen, diclofenac and ibuprofen) was developed using two columns (Acclaim™ Trinity™ PI and Acclaim™ 120 Cig). Detectable concentrations of caffeine, acetaminophen, naproxen and diclofenac suggest that these organic contaminants could be a potential chemical marker for domestic sewage. This study showed that the combination of the distribution of organic contaminants and chemometric techniques is a promising approach in identifying the sources of contamination and this information would be helpful for the local authorities to take action in managing environmental pollution.